Infusing Adult Learning Theory in a Traditional University Classroom: An Alternate Approach to Freshman Orientation - Jake Ayo; Kenda Grover (Adult Education Research Conference, 2015)
The purpose of this study was to measure differences in freshmen expectations between the first and last days of a required 8-week orientation course. The course was taught using adult learning theory as a framework, incorporating adult learning principles as instructional strategies for a traditional population of learners.
Keywords: adult education; autonomous learning; independent learning